Adherence to antihypertensive therapy in patients over 60 years old - Santiago A. López Vázquez; Raúl Chávez Vega (Universidad de Ciencias Médicas de La Habana, 2015)
Introduction: although the treatment of Hypertension reduces complications and mortality from this disease, about 30% of hypertensive patients are not well controlled. Failure of treatment is considered the responsible and main factor for the poor control of the disease. Objective: to characterize adherence to antihypertensive treatment of patients over 60 years at Consulting room 16, in "26 de Julio" Polyclinic, Havana. Material and Method: a descriptive cross-sectional research, in 245 hypertensive patients over 60 years with drug treatment was performed. The variables studied were: age, biological sex, educational level, prescribed treatment, and treatment adherence and non-adherence reason. Results: adherence to treatment was 58.3%. Patients with university level of education had 74% adherence. The daily treatment regimen of one drug had greater adherence to 73.8%. The increased adhesion was found in patients taking drugs with one daily dose: Atenolol (92.3%), Amlodipino (88.9%) or Enalapril (88.1%). Among the most frequent reasons for non-adherence to treatment were found to miss the doses (40%) and feeling good(38.2%). Conclusions: adherence to therapy of hypertensive patients over 60 years is low. This problem is caused by several factors, mainly forgetting medication intakes, the dosing with a great number of medicines and poor perceptions of health risk which means inadequate control of the disease.  Keywords: hypertension, adherence to therapy, pharmacological treatment, antihypertensive